Assesing Critical Thinking Skills in Dynamic Fluids at Senior High School: Rasch Model Analysis - Afandi, Achmad; Aviyanti, Lina; Saepuzaman, Duden; Setiawan , Andhy (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2025)
This study aims to measure critical thinking skills in fluid dynamics using the Rasch Model analysis. Critical thinking skills are very important in science education, especially physics, which requires analytical and evaluative skills to understand real phenomena. This measurement tool is designed to measure students' understanding of critical thinking in fluid dynamics. The method used in this study is quantitative and descriptive. The measurement instrument consists of 15 multiple-choice questions on fluid dynamics material analyzed using Winsteps version 3.73. The sample consisted of 250 students from several high schools in Mojokerto, East Java. The results show that the overall validity of the items is acceptable. The items are valid and can be used as a whole; their reliability is good. Item difficulty analysis based on logit and Wright maps showed that no items were the most difficult. Items in the moderate category were 8, 7, 4, and 13. The ICC plot showed that all items were normally distributed, indicating they conformed in the Rasch model. In addition, the DIF graph showed that there was no gender bias in any of the items, so that neither male nor female students had an advantage.